Effects of SCP-SCP-T Exercise on Improving Throwing Performance of Senior Javelin Throwing Athletes (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2025)
Athlete achievement in javelin throwing is ideally determined by various factors, including adequate physical ability, good technique, and the selection of appropriate training methods. This study aimed to analyse the effect of Standing Cable Pullover-Standing Cable Pullover-Torso (SCP-SCP-T) training on improving javelin throwing performance. The research method used experimental research. The population of this study were senior javelin throwers. The sampling technique used random sampling. The samples of this study were divided into two groups, including 10 athletes in the Standing Cable Pullover-Standing Cable Pullover-Torso (SCP-SCP-T) group and 10 athletes for the control group. The research instruments included weight scale for measuring body weight and javelin throwing ability test, with validity 0.998 and reliability 0.999, for measuring javelin throwing performance. Data analysis was processed using descriptive statistical tests, normality tests, homogeneity tests, and Ancova tests. The results found a more significant effect of the SCP-SCP-T training model on improving throwing performance than the training performed in control group with a P-value = 0.017 0.05. This study concluded that the modified SCP-SCP-T exercise can improve javelin throwing performance. The results of this study can be the basis for consideration of training methods to improve sport skills.